IMPORTANT REASONS AND EFFORT TO BUILD SCHOOL WORK AND COMMITTEE HARMONY - Triwiyanto, Teguh; Kusumaningrum, Desi Eri (Acta Scientiae et Intellectus, 2024)
The purpose of research is important to know the reasons and the efforts to build school work and school committee harmony. Pamekasan research sites in East Java province with research subjects principals and elementary school committee chairman as many as 44 people from 28 primary schools. The research method uses a quantitative approach using descriptive analysis and technical analysis of Pearson product moment correlation. The results show how many reasons there are important and efforts to build school work and school committee harmony. There is a relationship between the importance and the efforts to build school work and school committee harmony with a correlation coefficient of 0.986.